Exercise testing and postoperative complications after minimally invasive lung resection: A cohort study - Chouinard, Gabriel; Roy, Pascalin; Blais, Marie-Christine; Lippens, Alexandre; Pelletier, Éliane; Roy, Emma; Marcoux, Mathieu; Ugalde, Paula A.; Rheault, Justine; Pigeon, Marc-Antoine; Nicodème, Frédéric; Lacasse, Yves; et al. (Frontiers in Physiology, 2022)
Background. Peak oxygen uptake (VO2) during cardiopulmonary exercise testing (CPET) is used to stratify postoperative risk following lung cancer resection but peak thresholds to predict post-operative mortality and morbidity were derived mostly from patients who underwent thoracotomy. Objectives. We evaluated whether peak VO2 or other CPET-derived variables predict post-operative mortality and cardiopulmonary morbidity after minimally invasive video-assisted thoracoscopic surgery (VATS) for lung cancer resection. Methods. A retrospective analysis of patients who underwent VATS lung resection between 2002 and 2019 and in whom CPET was performed. Logistic regression models were used to determine predictors of postoperative outcomes until 30 days after surgery. The ability of peak VO2to discriminate between patients with and without post-operative complications was evaluated using Receiver operating characteristic (ROC) analysis. Results. Among the 593 patients, postoperative cardiopulmonary complications occurred in 92 (15.5%) individuals, including three deaths. Mean peak VO2 was 18.8 ml/kg/min, ranging from 7.0 to 36.4 ml/kg/min. Best predictors of postoperative morbidity and mortality were peripheral arterial disease, bilobectomy or pneumonectomy (versus sublobar resection), preoperative FEV1, peak VO2, and peak VE/VCO2. The proportion of patients with peak VO2 of < 15 ml/kg/min, 15 to < 20 ml/kg/min and ≥ 20 ml/kg/min experiencing at least one postoperative complication was 23.8, 16.3 and 10.4%, respectively. The area under the ROC curve for peak VO2 was 0.63 (95% CI: 0.57 to 0.69). Conclusion. Although lower peak VO2 was a predictor of postoperative complications following VATS lung cancer resection, its ability to discriminate patients with or without complications was limited.